Creating Inclusive Classrooms for Highly Dysregulated Students: What Can We Learn from Existing Literature? - Emma Goodall; Charlotte Brownlow; Erich C. Fein; Sarah Candeloro (MDPI AG, 2022)
The ability to self-regulate is a key focus for educators, especially for neurodivergent students, such as those with ADHD, fetal alcohol syndrome, mental health difficulties, autism, and/or anxiety. Students not being able to self-regulate frequently results in their behaviours being labelled as "naughty" or "challenging" by teachers. Continued dysregulation can lead to periods of suspension and exclusion, impacting both attendance rates for students and their broader families. Previous research has shown that the impacts of poor self-regulation can be wide-ranging, spanning both social and academic outcomes. The broad negative impact of poor self-regulation means that it is important to support families and classroom teachers to effectively improve children's self-regulation. However, to support families and educators, there is a need to develop and deploy a theoretical framework to suggest why self-regulation may be under-developed and, conversely, how self-regulation may be effectively developed across a wide range of contexts. This paper considers current literature exploring the links between individual experiences of emotions and connections with core abilities of interoception, self-regulation, emotional intelligence, and metacognition. It outlines a hypothesised model of how these abilities intertwine and how supporting core building blocks within educational settings can enable supportive and inclusive educational contexts, providing positive experiences for students and teachers alike.